Multipurpose Drugs Active Against Both Plasmodium spp. and Microorganisms: Potential Application for New Drug Development - Endo, Takuro; Takemae, Hitoshi; Sharma, Indu; Furuya, Tetsuya (Frontiers in Cellular and Infection Microbiology, 2021)
Malaria, caused by infection of protozoan parasites Plasmodium spp., is still causing serious problems in endemic regions in the world. Although WHO recommends artemisinin combination therapies for treatment of malaria patients, emergence of artemisinin-resistant parasites has become a serious issue and underscores the need for development of new anti-malarial drugs. On the other hand, new- and re-emergences of infectious diseases, such as pandemic influenza, Ebola virus disease and COVID-19, are urging the world to develop effective chemotherapeutic agents against the causative viruses, which are not achieved to the desired level yet. In this review article, we describe existing drugs which are active against both Plasmodium spp. and microorganisms including viruses, bacteria and fungi. We also focus on the current knowledge about the mechanism of actions of these drugs. Our major aim of this article is to describe examples of drugs that kills both Plasmodium parasites and other microbes and to provide valuable information to help finding new ideas for developing novel drugs, rather than merely augmenting already existing drug repurposing efforts.